Susceptibility to Community Associated Methicillin Resistant Staphylococcus Aureus: A Preliminary Study - Xian, Gan Ee; Megantara, Imam; Gondodiputro, Sharon (Althea Medical Journal, 2018)
Background: The Staphylococcus aureus infection is a leading cause of infection around the world. Due to the introduction of antibiotics, a strain called Methicillin-resistant S. aureus (MRSA) has emerged and occured in hospitalized patients worldwide. However around 1990, this infection had been detected among healthy people in the community without previous health care contact, known as community associated MRSA (CA-MRSA). The objectives of this study was to identify the susceptibility to CA-MRSA among people who came to Puskesmas Jatinangor, West Java, Indonesia.Methods: A descriptive study using purposive sampling was carried out from September to October 2014 with data obtained through anterior nasal swab of 65 patients from Puskesmas Jatinangor who fulfilled the exclusion and inclusion criteria. Samples were transported to the microbiology lab of Faculty of Medicine Universitas Padjadjaran and planted on blood agar for culturing, then identified through gram staining, catalase and coagulase tests. Lastly tested for antibiotic resistance and the zone of inhibition measuring â¤21mm were classified as positive MRSA. The collected data were presented using tables.Results: Out of 65 samples that were collected and tested, 17 samples (26%) were Staphylococcus aureus (S. aureus) carriers; 6 samples (9%) were positive with MRSA isolates; 6/17 of the S. aureus are MRSA.Conclusions: People who come to Puskesmas Jatinangor show a significantly high proportion of susceptibility to CA-MRS.